Syntheses, structures and antimicrobial properties of complexes based on 2-hydroxybenzaldehyde-4-aminoantipyrine Schiff base. Issue 4 (23rd March 2021) - Tang, Quan; Hu, Jing; Ding, Yi-Jie; Zhang, Yi-Fan; Li, Hui-Fang; Xu, Ming; Yang, Xin-Cheng; Liang, Lili; Li, Wen-Ge
Abstract: Two monomeric complexes, [NiL2 ·3H2 O] (1 ) and [Nd2 L3 (NO3 )3 ] (2 ), with a tridentate ONO-donor Schiff base ligand HL (HL = 2-hydroxybenzaldehyde-4-aminoantipyrine) have been synthesized. Single-crystal X-ray diffraction analysis indicates that the asymmetric unit of 1 contains one Ni(II) and two L − ligands, while 2 consists of two Nd(III) ions, three L − ligands, and three NO3 − ions. Complexes 1 and 2 are both 0-D discrete monomers, and there are intermolecular π–π interactions in 1 and intramolecular π–π interactions in 2 . The discrete [NiL2 ·3H2 O] monomers are further connected through π–π interactions, resulting in a 3-D supramolecular structure. Powder XRD and TG-DSC were performed for 1 and 2 . Antimicrobial experiments show that 1 displays significant antibacterial effect against Bacillary dysentery and Escherichia coli in comparison with that of Schiff base ligand. Graphical Abstract: